Effect of macroeconomic variables on systemic risk: Evidence from Vietnamese economy - Tram, Thi Xuan Huong; Thi Thanh Hoai, Nguyen (Economics and Business Letters, 2021)
This paper aims to find out the relationship between systemic risk in Vietnam and the effects of macroeconomic factors, including exchange rate, interest rates, and economic growth. We collect data from the Vietnamese stock market, specifically 29 listed financial firms (banks, insurance companies, and securities firms) for the period 2010-2018. The analysis is performed in two steps including systematic risk measurement in Vietnam based on the Systemic Expected Shortfall (SES) method and providing evidence from analysis related to the risk determinants assessment. Besides ordinary least squares (OLS) methods, we make use of fixed-effects (FEM) estimations, random-effects (REM) estimations, and system generalized method of moments (SGMM). The empirical evidence in this paper indicates that economic growth has a negative relationship on systemic risk in Vietnam while the exchange rate has a positive impact on systemic risk, and the interest rate has a negative relationship on systemic risk in Vietnam. Future studies can address the effects of interest rate on systemic risk during this period.